2005
DOI: 10.1111/j.1468-3083.2005.01345.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of paraneoplastic pemphigus with Rituximab: a case report and review of literature

Abstract: Paraneoplastic pemphigus (PNP) is an autoimmune blistering disease with poor prognosis when associated with malignant neoplasm. We report the case of a patient with PNP associated with a CD20+ non-Hodgkin follicular lymphoma who was treated with Rituximab plus corticosteroids and short courses of cyclosporin. One and a half years after Rituximab therapy, oral ulcerations had cleared and oral methylprednisolone was slowly tapered down without further recurrences. In the course of the disease, the patient develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 31 publications
0
47
1
3
Order By: Relevance
“…29,31 Paraneoplastic pemphigus carries a poor prognosis, with a 2 year 90% mortality rate. 29 Bullous pemphigoid is characterized by tense, subepidermal, blisters of the skin due to antibodies against basement membrane antigens, bullous pemphigoid antigens 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29,31 Paraneoplastic pemphigus carries a poor prognosis, with a 2 year 90% mortality rate. 29 Bullous pemphigoid is characterized by tense, subepidermal, blisters of the skin due to antibodies against basement membrane antigens, bullous pemphigoid antigens 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…14 In the previous studies of IVIg treatment for patients with pemphigus, it was reported that the autoantibody titers did reduce during the treatment. 16 Rituximab was originally developed to treat refractory, low-grade, follicular, B cell non-Hodgkins lymphoma 2 , but has been used experimentally in various autoimmune diseases including autoimmune blistering disorders (pemphigus vulgaris, 5-7,9-10,12,14,17-27 pemphigus vegetans, 12 pemphigus foliaceus, 5,8,11,12,28 paraneoplastic pemphigus, [29][30][31][32][33] bullous pemphigoid, 34 and epidermolysis bullosa acquisita 13,35,36 …”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Because our patient had follicular lymphoma, we performed eight cycles of rituximab treatment. 13 The rituximab treatment reduced B cells that produced anti-Before BD After BD desmogleins-1 and -3, and BP180 antibodies, leading to the remission of PNP.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was previously reported that an anti-CD20 antibody, rituximab, successfully induced remission in many patients with pemphigus accompanying follicular lymphoma. [4][5][6] Bronchiolitis obliterans (BO) is an irreversible and lethal lung disease that occurs in chronic graft-versus-host disease patients after allogeneic hematopoietic stem cell transplantation. It was also reported that 30-40% of patients with PNP progress to BO, which represents the major cause of death.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] B-lymphocytes express the CD20 molecule and can be selectively removed by the use of anti-CD20 therapeutic antibodies such as rituximab. Several recent studies have demonstrated the efficacy of this approach; some patients have long lasting remission after a single course of treatment.…”
Section: Monoclonal Antibody Therapymentioning
confidence: 99%